2016
DOI: 10.1002/mc.22533
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biomarker expression between proximal and distal colorectal adenomas: The Tennessee–Indiana Adenoma Recurrence Study

Abstract: It is unclear if proximal and distal traditional adenomas present with differences in molecular events which contribute to cancer heterogeneity by tumor anatomical subsite. Participants from a colonoscopy-based study (n=380) were divided into subgroups based on the location of their most advanced adenoma: proximal, distal, or “equivalent both sides”. Eight biomarkers in the most advanced adenomas were evaluated by immunohistochemistry (Ki-67, COX-2, TGFβRII, EGFR, β-catenin, cyclin D1, c-Myc) or TUNEL (apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Another immunohistochemical study was performed in 380 adenomas for differences in molecular Ki-67, COX-2, TGFβRI, EGFR, β-catenin, cyclin D1, c-MYC and TUNEL (apoptosis) mutations of proximal and distal adenomas, which may contribute for cancer heterogeneity between the two topographies. The authors concluded that the adenoma location is not one of the main determiners of expression of the analyzed biomarkers outside of other pathological features 21 . Another research evaluated the expression of 29 markers of 50 patients pairing their neoplastic tissue (from adenoma to hepatic metastasis) with a normal mucosa sample.…”
Section: Discussionmentioning
confidence: 98%
“…Another immunohistochemical study was performed in 380 adenomas for differences in molecular Ki-67, COX-2, TGFβRI, EGFR, β-catenin, cyclin D1, c-MYC and TUNEL (apoptosis) mutations of proximal and distal adenomas, which may contribute for cancer heterogeneity between the two topographies. The authors concluded that the adenoma location is not one of the main determiners of expression of the analyzed biomarkers outside of other pathological features 21 . Another research evaluated the expression of 29 markers of 50 patients pairing their neoplastic tissue (from adenoma to hepatic metastasis) with a normal mucosa sample.…”
Section: Discussionmentioning
confidence: 98%